2016
DOI: 10.1021/acs.jpcc.5b12606
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State NMR Investigations of MgCl2 Catalyst Support

Abstract: MgCl2 is a vital component of Ziegler-Natta catalysts for olefin polymerization. Here we:synthesized anhydrous MgCl2 using different drying protocols and exploited H-1 NMR to quantify the proton content. We report on our study of neat and ball-milled MgCl2 samples by means of Mg-25 and Cl-35 solid-state NMR. DFT calculations of the quadrupole tensor aid in analysis of the spectra. The results show that, due to the morphology of the neat particles, a preferred Orientation is induced which manifests itself in un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 82 publications
3
41
0
Order By: Relevance
“…In a previous publication, we showed that even thoroughly dried neat MgCl 2 samples are not completely water-free. 40 In fact, a full surface coverage of water or otherwise protonated species (−OH surface groups) was found. The binary adducts presented in this study have significantly larger surfaces areas ( Table 1 ) and might potentially take up large quantities of water.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous publication, we showed that even thoroughly dried neat MgCl 2 samples are not completely water-free. 40 In fact, a full surface coverage of water or otherwise protonated species (−OH surface groups) was found. The binary adducts presented in this study have significantly larger surfaces areas ( Table 1 ) and might potentially take up large quantities of water.…”
Section: Resultsmentioning
confidence: 99%
“… a ⟨ L c ⟩ and ⟨ L a ⟩ are the average particle dimension perpendicular and parallel to the basal ( ab ) plane, respectively. b See ref ( 40 ). c The average size could not be determined because the XRD diffraction peaks were too broad.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, for CLU‐24‐104/Me 2 O adducts this turned out to be complicated by the presence of multiple local minima with very similar energy values and low separation barriers, differing primarily in the local structure at corners with terminal Mg‐bonds; reversible or irreversible reconstructions from one such minimum to another were observed upon structure re‐optimization. The problem was overcome by adsorbing H 2 O molecules at the aforementioned corners, thus saturating the Mg coordination sphere; as is well‐known, H 2 O is an ubiquitous donor with high affinity for MgCl 2 (vide infra), and a common contaminant of real MgCl 2 adducts . ‘Corner‐stabilized’ CLU‐24‐104/Me 2 O adducts did not feature any propensity to reconstruct (for details, see the SI).…”
Section: Results Annd Discussionmentioning
confidence: 99%
“…In all cases, notably, based on the calculated values of adsorption energy (Table ), one should expect surface saturation at room temperature to occur at a donor partial pressure as low as 1 ppb. For the specific case of H 2 O, this should be kept in mind when handling model samples of ‘activated’ MgCl 2 for fundamental (e.g., spectroscopic) studies; whereas preventing surface saturation might be feasible in a UHV cell, it certainly is not in a glove‐box …”
Section: Results Annd Discussionmentioning
confidence: 99%